Studi docking untuk skrining senyawa antibakteri dari Jeringau Merah (Acorus calamus L.) menggunakan protein Shigella flexneri sebagai model sistem - Riyadh Aqilsya Amaryl Dyas; Bambang Wijianto; Hariyanto IH (Acta Chimica Asiana, 2023)
Alpha (a) and beta (β) asarone were identified as the main compounds of red Jeringau (Acorus calamus L.) and had antimicrobial properties. This study aimed to know these two compounds' antibacterial mechanism and toxicity prediction against the PBP 2 protein and 50S Ribosomal Protein of Shigella flexneri. Molecular docking protocol using PyRx device was performed with Exhaustiveness value= 106, grid x=38.738375, y=112.645792, z=46.926417 for PBP2, and grid x=71.721251, y=47.551601, z=9.663173 for 50S Ribosomal Protein. The molecular docking results on the α -Asarone compound obtained an affinity value of -5.7 kcal/mol for PBP2 and an affinity value of -5.6 kcal/mol for 50S Ribosomal Protein. In comparison, β-Asarone had an affinity value of -5.6 kcal/mol to PBP2 and an affinity value of -5.7 kcal/mol for 50S Ribosomal Protein. The α and β-Asarone affinity had better values than the control. Molecular docking of α and β-Asarone compounds results in ionic bonds to the TYR529 amino acid and polar bonds to the ASN552 amino acid of PBP2. However, only β-Asarone produces ionic bonds at the amino acid ILE17 and polar bonds at GLU13 from 50S Ribosomal Protein. Based on this study, the α and β-Asarone compounds were shown to have antibacterial activity by interfering with the permeability of the bacterial cell wall. Both compounds are also predicted to have carcinogenic and mutagen effects.